FRI0716-HPR Assessing the burden of treated and untreated osteoarthritis pain in europe. (12th June 2018) - Doane, M.J.; Jaffe, D.H.; Dragon, E.; Abraham, L.; Viktrup, L.; Bushmakin, A.G.; Cappelleri, J.C.
Abstract : Background: Osteoarthritis (OA) is a chronic, progressive musculoskeletal condition, estimated to affect >40 million people across Europe. OA is a major challenge for health care systems worldwide and is a leading contributor to years lived with disability (YLD) globally. 1 Current pharmacological treatment options may provide limited pain relief or may not be appropriate for long-term use in all patients because of adverse events. 2 There are few studies on the burden of chronic pain due to OA in Europe and whether this burden varies for those being treated with prescription (Rx) treatments compared with those who are not Rx treated. Objectives: To assess the burden of OA in Europe and to determine whether burden differs by pain severity and treatment status. Methods: A retrospective, cross-sectional study was conducted using data from the 2016 and 2017 National Health and Wellness Survey (NHWS) from five European Union countries (5EU): France, Germany, Italy, Spain, and United Kingdom. NHWS respondents with a self-reported OA diagnosis who completed the pain module were identified. Neuropathic and phantom limb pains were excluded. OA respondents were categorized into 4 groups by severity of pain and treatment: moderate/severe Rx-treated [M/S-Treated]; moderate/severe Rx-untreated [M/S-Untreated]; Mild Rx-treated; and Mild Rx-untreated (reference group). Outcomes of interest included health-related quality of life (HRQoL) (SF-12v2: mental and physical component summary scores [MCS, PCS]), health status (EQ-5D), productivity loss (Work Productivity and Activity Impairment [WPAI] questionnaire), and healthcare utilization in past 6 months. Multivariable analyses adjusted for baseline differences between groups (e.g., demographic and health characteristics). Results: 2, 417 OA patients reported a mean age of 61.8 (SD=10.8) years and the majority was female (64.5%). Sixty-percent of OA patients had M/S pain (n=1, 440). Stratification by pain and treatment groups resulted in the following: M/S-Treated=27.4%, M/S-Untreated=32.2%, Mild-Treated=22.3%, and Mild-Untreated=18.2%. Those with M/S pain severity, both Rx treated and untreated, showed significantly worse HRQoL, health status and work impairment compared with the reference group (table 1). Further, both Rx treated groups had significantly more health care provider visits compared with OA patients without a Rx. Conclusions: The majority of European patients with OA in this study reported moderate-severe pain irrespective of prescription treatment. Whether treated or untreated, those with moderate to severe OA pain demonstrated a substantial burden on quality of life, health status, and productivity compared with those with mild pain. References: 1. Osteoarthritis Research Society International (OARSI). Osteoarthritis: A Serious Disease. New Jersey: December 2016. 2. Noble M, et al. Cochrane Database of Systematic Reviews 2010;1:Art. No. CD006605. Disclosure of Interest: M. Doane Grant/research support from: Pfizer Ltd., D. Jaffe Grant/research support from: Pfizer Ltd., E. Dragon Employee of: Pfizer Ltd., L. Abraham Employee of: Pfizer Ltd., L. Viktrup Employee of: Eli Lilly & Company, A. Bushmakin Employee of: Pfizer Ltd., J. Cappelleri Employee of: Pfizer Ltd.